Virtual Frame by 3. - Büchel, Daniel; Büchel, Heinrich; Dreher, Sabine; Eckert, Robert; Gehrmann, Lucas; Kühne, Roger; Manner, Boris; Matt, Gerald; Muhr, Christian; Reder, Christian; Thoma, Berthold (Wien : Kunsthalle Wien, 2004)
Alien Productions ; Appelt, Siegrun ; Aschauer, Michael ; Blokes ; Delaware ; Experimental Jetset ; Feuerstein, Thomas ; Hellsten, Torbjörn ; Honetschläger, Edgar ; Insertsilence ; Jermolaewa, Anna ; Kaplan, Geoff ; Kartan, Oliver ; Kilián, Juraj ; Kogler, Peter ; Kopeinig, Boris ; Körner Union ; Kram, Reed ; Lehni, Jürg ; Mandl, Rainer ; Masaru Ishiura ; Mayr, Elke ; Muzak ; Oishi, Akinori ; Reala ; Robinson, Craig ; Ruhm, Constanze ; Schwarz, Christoph ; Schwarz, Gertraud ; Stumpo, Niko ; TGB Design ; The Designers Republic ; Tomato ; Tomic, Milica ; Tossin, Clarissa ; Tylevich, Alexei ; Wachsmuth, Arye ; Walking Chair ; Watz, Marius ; Weibel, Peter ; Wildling, Elisabeth ; Worthington, Michael ; Wurm, Erwin ; Zobernig, Heimo
biog. per kunstenaar
Duits
Engels
Exhibition. Virtuali Frame by 3. Kunsthalle Wien. 24.02.2004 - 07.03.2004.
boek